PENERAPAN PENGENDALIAN KUALITAS PRODUK UNTUK MENGOPTIMALKAN JUMLAH PRODUKSI - Demmanggasa, Yultan; Sampe, Rafilus (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2022)
The purpose of implementation of product quality control is to optimize the amount of production. That is to know more in the matter of product proportion which is not in accordance with the quality and to know the cause of error in production process. The results achieved of an implementation of product quality control is to optimize amount of production and also knowing the main cause of product which is not suitable with the quality of the resulting product.